(4x+3)(4x+3)=7

Simple and best practice solution for (4x+3)(4x+3)=7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (4x+3)(4x+3)=7 equation:


Simplifying
(4x + 3)(4x + 3) = 7

Reorder the terms:
(3 + 4x)(4x + 3) = 7

Reorder the terms:
(3 + 4x)(3 + 4x) = 7

Multiply (3 + 4x) * (3 + 4x)
(3(3 + 4x) + 4x * (3 + 4x)) = 7
((3 * 3 + 4x * 3) + 4x * (3 + 4x)) = 7
((9 + 12x) + 4x * (3 + 4x)) = 7
(9 + 12x + (3 * 4x + 4x * 4x)) = 7
(9 + 12x + (12x + 16x2)) = 7

Combine like terms: 12x + 12x = 24x
(9 + 24x + 16x2) = 7

Solving
9 + 24x + 16x2 = 7

Solving for variable 'x'.

Reorder the terms:
9 + -7 + 24x + 16x2 = 7 + -7

Combine like terms: 9 + -7 = 2
2 + 24x + 16x2 = 7 + -7

Combine like terms: 7 + -7 = 0
2 + 24x + 16x2 = 0

Factor out the Greatest Common Factor (GCF), '2'.
2(1 + 12x + 8x2) = 0

Ignore the factor 2.

Subproblem 1

Set the factor '(1 + 12x + 8x2)' equal to zero and attempt to solve: Simplifying 1 + 12x + 8x2 = 0 Solving 1 + 12x + 8x2 = 0 Begin completing the square. Divide all terms by 8 the coefficient of the squared term: Divide each side by '8'. 0.125 + 1.5x + x2 = 0 Move the constant term to the right: Add '-0.125' to each side of the equation. 0.125 + 1.5x + -0.125 + x2 = 0 + -0.125 Reorder the terms: 0.125 + -0.125 + 1.5x + x2 = 0 + -0.125 Combine like terms: 0.125 + -0.125 = 0.000 0.000 + 1.5x + x2 = 0 + -0.125 1.5x + x2 = 0 + -0.125 Combine like terms: 0 + -0.125 = -0.125 1.5x + x2 = -0.125 The x term is 1.5x. Take half its coefficient (0.75). Square it (0.5625) and add it to both sides. Add '0.5625' to each side of the equation. 1.5x + 0.5625 + x2 = -0.125 + 0.5625 Reorder the terms: 0.5625 + 1.5x + x2 = -0.125 + 0.5625 Combine like terms: -0.125 + 0.5625 = 0.4375 0.5625 + 1.5x + x2 = 0.4375 Factor a perfect square on the left side: (x + 0.75)(x + 0.75) = 0.4375 Calculate the square root of the right side: 0.661437828 Break this problem into two subproblems by setting (x + 0.75) equal to 0.661437828 and -0.661437828.

Subproblem 1

x + 0.75 = 0.661437828 Simplifying x + 0.75 = 0.661437828 Reorder the terms: 0.75 + x = 0.661437828 Solving 0.75 + x = 0.661437828 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.75' to each side of the equation. 0.75 + -0.75 + x = 0.661437828 + -0.75 Combine like terms: 0.75 + -0.75 = 0.00 0.00 + x = 0.661437828 + -0.75 x = 0.661437828 + -0.75 Combine like terms: 0.661437828 + -0.75 = -0.088562172 x = -0.088562172 Simplifying x = -0.088562172

Subproblem 2

x + 0.75 = -0.661437828 Simplifying x + 0.75 = -0.661437828 Reorder the terms: 0.75 + x = -0.661437828 Solving 0.75 + x = -0.661437828 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.75' to each side of the equation. 0.75 + -0.75 + x = -0.661437828 + -0.75 Combine like terms: 0.75 + -0.75 = 0.00 0.00 + x = -0.661437828 + -0.75 x = -0.661437828 + -0.75 Combine like terms: -0.661437828 + -0.75 = -1.411437828 x = -1.411437828 Simplifying x = -1.411437828

Solution

The solution to the problem is based on the solutions from the subproblems. x = {-0.088562172, -1.411437828}

Solution

x = {-0.088562172, -1.411437828}

See similar equations:

| 98x^2= | | (x+5)(x+5)=20 | | (x+3)(x+3)=44 | | (x+5)(x+5)=12 | | (5x+5)(5x+5)=100 | | 9x^2-12y+4=0 | | 4p+2=2p+10 | | x^2-5=20 | | (x+6)(x+6)=11 | | 14x+23=4x+174 | | 5277.356*85.36= | | (3x+3)(3x+3)=36 | | 3x+2y=50 | | 8-2(a+2)=a+7 | | 16t^2+36t-8=0 | | 12x^2+2x=24 | | 2x^2+5=2 | | a^2-5a=24 | | x^2-49=28 | | -1=3w-7 | | 227-4x=32x+19 | | 13-7x=213-42x | | 2(3n+3)=-10 | | -9=3x+9 | | 13*21= | | 6y^2-19y+15=0 | | 85-6x=10-7x | | x^3-x^2-10=0 | | 96-3x=5x+8 | | X+4=3x-6 | | (12-4x)+(5-7x)=23 | | x^3+3*x+2=0 |

Equations solver categories